Interactions that determine the assembly of a retinoid X receptor/corepressor complex - Ghosh, Jagadish C. (The National Academy of Sciences, 2002)
The retinoid X receptor (RXR) is a key regulator in multiple signaling pathways because it can form either a homodimer with itself or a heterodimer with members of the class I nuclear receptors. The RXR-containing dimers regulate transcription by recruiting coactivators or corepressors to the target promoters. The binding of coactivators to RXR is mediated through a hydrophobic pocket formed in part by the C-terminal activation helix (AF-2). However, little is known about interactions of corepressors with RXR and its roles in transcriptional repression. Here we show that the repression activity of RXR correlates with its binding to the corepressor silencing mediator for retinoid and thyroid hormone receptors (SMRT). This intrinsic repression activity is masked by the AF-2 helix, which antagonizes SMRT binding. Inhibition of SMRT binding by the AF-2 helix requires specific amino acid sequences and the helical structure. Furthermore, the SMRT-binding site on RXR is independent of helix 11 but overlaps with the coactivator-binding pocket. On the basis of these results, we propose a structural model to help understand the molecular mechanism of corepressor recruitment by RXR.